Saturday, 15 June 2019 2019
DOI: 10.1136/annrheumdis-2019-eular.7601
|View full text |Cite
|
Sign up to set email alerts
|

Sat0144 understanding the Long-Term Outcome of Rituximab – Implications for Management

Abstract: Background:In patients with rheumatoid arthritis (RA), rituximab (RTX) is often prescribed after loss of response to TNF inhibitors; however, little is known about the long-term outcome of patients receiving treatment with RTX. Previous work [1,2] has shown that aiming for “complete B-cell depletion with clinical response” (CD-R) leads to an optimal management of the disease but unfortunately not all patients maintain this status. Whether CD-R can be regained with RTX retreatment remains unclear.Objectives:To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Early depth of B-cell depletion with clinical response leads to a better long-term outcome (27) but unfortunately, at some point almost half of the patients lose CD-R with subsequent cycles (53). An observational study (53) with over 700 patients treated with rituximab showed that 84% of those who lost CD-R can regained it with further treatment, with 77% of them doing so in the following cycle. Interestingly, 33% of patients that either lost clinical response or did not achieve complete B-cell depletion, never received further treatment with the drug and were switched to other therapies.…”
Section: Loss Of Response To Rituximabmentioning
confidence: 99%
“…Early depth of B-cell depletion with clinical response leads to a better long-term outcome (27) but unfortunately, at some point almost half of the patients lose CD-R with subsequent cycles (53). An observational study (53) with over 700 patients treated with rituximab showed that 84% of those who lost CD-R can regained it with further treatment, with 77% of them doing so in the following cycle. Interestingly, 33% of patients that either lost clinical response or did not achieve complete B-cell depletion, never received further treatment with the drug and were switched to other therapies.…”
Section: Loss Of Response To Rituximabmentioning
confidence: 99%